Nature in fragments : the legacy of sprawl - Johnson, Elizabeth A. (Elizabeth Ann), 1954 August 29-; Klemens, Michael W. (New directions in biodiversity conservation., 2005)
This new collection focuses on the impact of sprawl on biodiversity and the measures that can be taken to alleviate it. Leading biological and social scientists, conservationists, and land-use professionals examine how sprawl affects species and alters natural communities, ecosystems, and natural processes. The contributors integrate biodiversity issues, concerns, and needs into the growing number of anti-sprawl initiatives, including the "smart growth" and "new urbanist" movements.